Comparison of chlorination behaviors between norfloxacin and ofloxacin: Reaction kinetics, oxidation products and reaction pathways. (January 2019) - Wang, Xiaofeng; Li, Yin; Li, Ruiyang; Yang, Hongwei; Zhou, Beihai; Wang, Xiaomao; Xie, Yuefeng
Abstract: Fluoroquinolones (FQs) are very ubiquitous in water environment in China. The commonly application of free available chlorine (FAC) during water treatment stimulated the focus on the transformation of FQs during chlorination. Among these FQs, norfloxacin (NOR) and ofloxacin (OFL) are the representatives of secondary amine FQs and tertiary amine FQs, respectively. To better understand the difference between secondary amine FQs and tertiary amine FQs during chlorination, reaction kinetics, products and mechanisms were determined. The maximum k app of NOR were four orders of magnitude higher than that of OFL. Moreover, eleven products of NOR and twelve products of OFL were obtained by LC−MS/MS analysis. For the two FQs, the common reactive sites were three nitrogen atoms, benzene ring, carboxyl group and double bond by chlorination. For OFL, the ether ring was also active in aqueous system. The formation mechanisms of these products were presented in this study. The main reaction pathways were electrophilic addition to nitrogen, nucleophilic substitution to benzene ring, halodecarboxylation of carboxyl group and hydrolysis of ether ring. Na2 S2 O3 as a reducing agent had large effect on the chlorination of secondary amine FQ, but no effect on tertiary amine FQ. Be different to secondary amine FQ, the opening of quinolone ring happened in tertiary amine FQ after halodecarboxylation of carboxyl group. Graphical abstract: Highlights: The maximum k app of NOR were 4 orders of magnitude higher than that of OFL. The reactions of deprotonated FQs species with HClO dominant the total reaction. The quinolone ring of tertiary amine FQ opened after halodecarboxylation.